Necessidades de cuidados: o olhar do paciente, acompanhante e equipe de enfermagem - Martins, Priscila Fernandes (2016)
Objectives: To access the patients´ perception and their level of satisfaction as well as their companions according to the care needs during hospitalization period; to observe the association of this level with sociodemographic variables and characteristics of hospitalization and the unity; to compare the care needs as realized by the patient and the Nursing team and investigate the sociodemographic factors associated with these perceptions. Methods: In the first stage, a descriptive exploratory study was performed in hospitals in the interior of São Paulo state, from March to May 2014; 411 patients and their companions participated. Afterwards, a comparative study in units and hospitalization was carried out in an extra–large capacity hospital in the state of São Paulo from April to July 2015. The subjects were 100 professionals (50 nurses and 50 technicians and nursing assistants) and 50 patients. A questionnaire was created and validated (for each stage) about care needs filled up by the participants. Results: The patients/companions ´ score of satisfaction ranged from 3.6 (0.4) to 4.6 (0.4). Emotional and spiritual needs (81 and 82%), security (83 and 67%) and attention (87 and 61%) were the most satisfied. An association was found between satisfaction and some sociodemographic variables and hospitalization characteristics. Considering the four areas investigated regarding the process of caring, the following variations were found: kw 0.32 (0.07 - 0.46) to kw 0.93 (0 - 0.40) for Planning and Care Organization; kw 0.56 (0 - 0.35) to 0.92 kw (0 - 0.39) for the Environmental Care; Kw 0.55 (0 - 0.32) to 0.96 kW (0 - 0.35) for Communication and Information and also kw 0.50 (0-0.20) to 0.93 (0.23 -0.64 for Basic Care. The domains of Environmental Care and Information and Communication received the highest percentage of kw values ≥ 0.61. Conclusions: Patients and their companions were satisfied with the service of care needs, however, some important areas showed a deficit of satisfaction. In general, it was observed alignment in meeting the care needs according to the patients´own view and nursing staff. However, the average satisfaction was found to be far below the desirable, underlying the need for much knowledge by the team on the caring needs of patients and participation of the patient and companion in decision-making. Information on the quality of received care can improve changes on the practice for the patient / family centered care.